International evidence on the determinants of trade credit provision. Issue 4 (8th April 2019) - Hill, Matt; Hill, Katerina; Preve, Lorenzo; Sarria-Allende, Virginia
Abstract : Purpose: The purpose of this paper is to examine whether the level of financial credit available in a country influences the level of trade credit provided to customers. Design/methodology/approach: The authors examine the association between the supply of trade credit and the availability of country-level private financial credit using multivariate regression models that account for country-level heterogeneity, macroeconomic conditions and firm-specific characteristics. The data set is a pooled sample of publicly traded firms incorporated in 66 countries. Findings: Supporting the re-distributional view of trade credit, robust results suggest that suppliers incorporated in countries with increased access to financial credit provide increased trade credit to their customers. Further results indicate significant differences in trade credit usage across geographical regions. Consistent with existing research using samples of US firms, the use of trade credit is correlated with firm-level measures of financial constraints and product market dynamics. Originality/value: The authors provide one of the first studies to examine differences in trade credit extension across a large number of countries.